Individualisation of cities as one of the factors of preserving human capital - E. A. Zakharchuk; V. E. Uporov (Вестник университета)
This study examines the problem of individualisation, individualisation of cities and its relationship with human capital. The strategies of Russian cities put human capital in one of the key positions, but the use of outdated methods of attracting the population has practically exhausted itself. In this regard, the authors put forward a hypothesis about a close connection between the individualisation of urban strategies and the preservation of human capital. Foreign approaches to the individualisation of cities have been considered. A mechanism for implementing individualised strategies of Russian cities by creating a city brand has been proposed as well as the key points of this process have been highlighted. The characteristic features of the formation of the brand of territories for different types of cities have been determined. It has been concluded that the manifestation of their individuality will help Russian cities in preserving human capital, as well as in attracting resources for their development.